Alterations to the synovial invaginations of the navicular bone are associated with pathology of both the navicular apparatus and distal interphalangeal joint when evaluated using high field MRI. Issue 1 (15th August 2022) - McParland, Thomas J.; Horne, Caitlyn R.; Robertson, James B.; Schnabel, Lauren V.; Nelson, Nathan C.
Abstract: Limited information exists regarding associations between distal interphalangeal joint (DIPJ) abnormalities and synovial invagination changes in the distal sesamoid (navicular) bone. This retrospective, analytical study aimed to measure specific characteristics of the synovial invaginations of the navicular bone to determine whether any single characteristic was associated with abnormalities in the DIPJ or navicular apparatus (NA) using high field MRI and a sample of 200 horses' feet. The DIPJ and NA were graded independently by three scorers. The grades were averaged, creating a global pathology score for the DIPJ, NA, and synovial invaginations. Higher global scores represented more severe pathology. The number of invaginations, depth of penetration, invagination shape, and cross‐sectional area (CSA) of the largest invagination were recorded. Interobserver agreement was measured using Cohen's Kappa. Associations of global scores of the DIPJ and NA with individual invagination characteristics were assessed using linear mixed modeling. A significant relationship was found between the number of invaginations and global DIPJ score, with higher invagination numbers associated with higher DIPJ scores. For invagination depth and CSA, a significant relationship was noted with global scores of both the DIPJ and NA. Reliable relationships between the shape of synovial invaginations and global scores of DIPJ and NA were not found, likely due to poor interobserver scoring (0.305). These findings suggest that primary DIPJ disease and NA pathology should be considered when noticing alterations to navicular synovial invaginations on MRI. This contrasts traditional views that synovial invagination abnormalities are indicative solely of NA pathology.